Perceptions on the environmental impacts of illegal river sand mining in the Limpopo Province, South Africa - Rapholo, Maropene Tebello Dinah; Rampedi, Isaac Tebogo; Sengani, Fhatuwani (Brawijaya University, 2024)
Illegal river sand mining in regions like the Limpopo Province poses severe threats to ecosystems and communities. Nevertheless, the community's perspectives concerning these effects have not been determined. Thus, the aim of the investigation was to assess community perceptions regarding the environmental consequences linked to river sand mining in the Limpopo Province, South Africa. The study employed mixed methods to acquire the primary data. The quantitative data were acquired using questionnaires; meanwhile, the qualitative data were collected through semi-structured interviews from various respondents. The demographic profile of the respondents indicated a predominantly male population, with a majority lacking formal qualifications. Additionally, the prevalence of very high unemployment rates in the area seemed to influence participation in the activity. Consequently, some perceived it as an economic opportunity to generate income for their sustenance. It has been found that as developments increase, the demand for river sand increases as well, leading to a high extraction rate of sand. Lastly, the extraction of the resources was found to be un-regulated or controlled; therefore, it is concluded that unregulated extraction of these resources resulted in a high extraction rate and environmental crises such as un-rehabilitated pits, water pollution, land pollution, among others. It is therefore recommended that collaborative efforts among relevant authorities to enforce stringent regulations and penalties. Equally vital are public awareness campaigns, which can play a pivotal role in educating communities about the environmental repercussions of illegal sand mining.